Experimental investigation on occurrence of gassy coal extrusion in coalmine. (March 2019) - Liu, Jie; Zhang, Ran; Song, Dazhao; Wang, Zaiquan
Highlights: Investigation on occurrence of gassy coal extrusion in coalmine is conducted. The occurrence of gassy coal extrusion is a long and slow development process. The development process of gassy coal extrusion can be divided into two stages. Radial support force, gas pressure and stress together determine coal failure. Abstract: Although the total death toll due to various accidents in China's coal mining industry has declined in recent years, gas accidents in coalmine, which are usually caused by gas explosions and outbursts, are still threatening miners' lives and property safety. Gassy coal extrusion, as an atypical gas accident, is bearing an increasing occurring frequency, especially in deep coalmine, and causing huge losses of human and property. In order to prevent the occurrence of atypical gas accidents, gassy coal extrusion, and ensure production safety, it is particularly important to investigate the development process of gassy coal extrusion. This study analyzed the changing rules of gas pressure and stress during the development process of gassy coal extrusion through a series of simulation experiments and found that the occurrence of gassy coal extrusion was a long and slow development process from shallow to deep. The development process can be divided into rapid stripping stage and slow fracturing stage; during the rapid stripping stage, the coal is stripped and broken into fragments due to rapid decrease of gas pressure and stress; during the slow fracturing stage, the coal fractures slowly and forms an arc-layered fracture resulting from slow release of gas pressure and stress transferring. Coal failure during the process of coal extrusion is determined by the gradual unloading of radial support force in the direction of extrusion, releasing of gas pressure and transferring of stress.